UNSTEADY 1D FLOW MODEL OF COMPOUND CHANNEL WITH VEGETATED FLOODPLAINS - Helmio T. (My University, 2002)
In areas that are occasionally inundated by floods, it is essential to know the quantity and density of vegetation that can be allowed while avoiding flooding beyond the intended floodplains. An unsteady flow model was developed for a channel with vegetated floodplains, to take into account the retention effects of the vegetated areas on flood wave conveyance. A one-dimensional (1D) unsteady flow model was combined with Nuding's method, which takes into account the friction caused by vegetation and the additional resistance caused by the interaction between the main channel and vegetated areas. Nuding's method was used to compute the total Darcy-Weisbach friction factor for each cross section and each water level as input data for each time step of the flow model. The model was applied to a double-trapezoidal channel, and the results were compared with a traditional model, in which floodplains were considered only as storage. Differences in the conveyance capacity of the channel were found between the models.
Keywords: HYDRAULICS; RIVERS; FLOODPLAINS; VEGETATION; ROUGHNESS